A High-Throughput Screening Method for Determining the Optimized Synthesis Conditions of Quinoxaline Derivatives Using Microdroplet Reaction - Yang, Yanmei; Liu, Junmin; Chen, Zhenzhen; Niu, Weihua; Li, Ran; Niu, Le; Yang, Peng; Mu, Xiaoyan; Tang, Bo (Frontiers in Chemistry, 2020)
Quinoxaline derivatives demonstrate many distinguished chemical, biological and physical properties and have a wide application in dyes, electroluminescent material, organic semiconductors, biological agents and etc. However, the synthesis of quinoxaline still suffer from several drawbacks, for instance, longer reaction time, unsatisfactory yields, use of metal catalyst. Here, utilizing microdroplet-assisted reactions, we demonstrate the successive synthesis of several important quinoxaline derivatives. For case studies of 1H-indeno [1, 2-b] quinoxaline, 3, 5-dimethyl-2-phenylquinoxaline, the present microdroplet approach can complete in milliseconds and the conversion rate reached 90% without adding any catalyst, which are considerably quicker and higher than the conversional bulk phase reactions. When combined to MS detector, high-throughput screening of the optimal reaction conditions can be achieved. Several impacts of droplet volume, reaction flow rate, distance from the MS inlet, spray voltage, and flow rate of the auxiliary gas can be screened on-site quickly for enhanced reaction speed and yields. More importantly, this platform is capable to be used for the scaled-up microdroplet synthesis of quinoxalines diversities. Considering the facile, economic, and environmentally friendly features of the microdroplet approach, we sincerely hope that the current strategy can effectively promote the academic research and industrial fabrications of functional quinoxaline substances for chemical, biological and pharmaceutical application developments.